New Insights into Novel Catalysts for Treatment of Pollutants in Wastewater - Xu, Hao; Liu, Yanbiao (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
This compilation of scientific work delves into innovative wastewater treatment technologies, focusing primarily on the development and optimization of novel catalysts for the effective removal of pollutants. Covering a range of catalysts, including precious metals and nanomaterials, the research offers new insights into cost-effective and efficient pollutant removal methods. Aimed at environmental scientists, engineers, and policymakers, this publication represents a significant contribution from top researchers in the field. It serves as a key resource for those looking to understand and apply the latest advancements in wastewater treatment.